Participatory Communication and Community Empowerment in Forum Bilikom: Non-Legal Constraints in Corporate–Community Deliberation - Dikhorir Afnan; Agus Irfan; Endah Nurhawaeny Kardiyati; Muhammad Kamaluddin (DAWUH : Islamic Communication Journal, 2026)
Participatory communication is widely recognized as a key component of community empowerment because it facilitates dialogue, mutual understanding, and collective problem-solving. However, the existence of participatory forums does not necessarily ensure meaningful community involvement. This study examines how non-legal constraints shape communication processes within an informal deliberative forum established through a corporate social responsibility program in Indonesia. Using a qualitative case study approach, the research analyzes patterns of participation, communication, and silence in a community–corporate communication forum. The findings reveal a gap between formal participation and substantive communicative engagement. Although the forum was designed to support dialogue, communication was largely characterized by one-way information dissemination, elite mediation, and culturally embedded norms of deference. These mechanisms limited reciprocity, discouraged critical expression, and reduced opportunities for meaningful participation. Consequently, community empowerment remained constrained despite the presence of formal participatory structures. This study contributes to participatory communication scholarship by demonstrating that communicative inequalities are often reproduced through socio-cultural and relational mechanisms rather than formal institutional restrictions. The findings underscore the importance of fostering more inclusive and dialogic communication processes to strengthen community empowerment and participatory governance.